Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Snorre til Sydpolen: 38 dager på isen (Status (Statoil), 1984)
Keywords: Dronning Maud Land; ekspedisjoner; geologi

Ressurser og storpolitikk: norske interesser i Antarktis - Andersen, Rolf Trolle (Komiteen, 1984)
Keywords: Antarktis; politikk

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

Marine and non-marine contribution to the chemical composition of snow at the Riiser-Larsenisen Ice Shelf in Antarctica - Gjessing, Yngvar (Atmospheric Environment (1967), 1984)
The distribution with depth of seven different ions in three snow profiles, 1, 60 and 120km from the coast on Riiser-Larsenisen Ice Shelf (72° 30′ S, 15°E) shows a close co-variation between ions of marine origin and non-correlation between these ions and ions of presumptively non-marine origin. The deposition rates of ions of marine origin vary as 50:1 over some 120 km distance from the coast. The SO42−Na+ ratio in snow near the coast is lower than for bulk sea water indicating a loss of SO42− in snow to the atmosphere by volatilization.
Keywords: Dronning Maud Land; geofysikk; geokjemi; isshelf; meteorologi

Factors Governing Pelagic Production in Polar Oceans - Sakshaug, Egil; Holm-Hansen, Osmund (Marine Phytoplankton and Productivity: Proceedings of the invited lectures to a symposium organized within the 5th conference of the European Society for Comparative Physiology and Biochemistry — Taormina, Sicily, Italy, September 5–8, 1983, 1984)
Keywords: Sørishavet; fytoplankton; havis; krill; planteplankton; primærproduksjon; sjøis; sjøvann

Ti nye år: Vestfold Historielag 60 år - Thoresen, Per (Vestfoldminne, 1984)
Keywords: Sørishavet; hvalfangst; kulturhistorie; pelagisk

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi